Embracing WhatsApp Application as Emergency Remote Learning During Covid 19 Pandemic - Yasyir Fahmi Mubaraq*; Hidya Maulida; Yulieda Hermaniar; Lianada Rizky (Riwayat: Educational Journal of History and Humanities, 2023)
This paper pictures education changes into a technological system. Face to face class has to be limited because of the pandemic. In Indonesia, online learning is something new that needs adaptation to do because not all students are familiar with the system. Some students got some difficulties during online learning and students also have different views of this learning system. Emergency remote teaching (ERT) is meant to be a temporary shift from the normal modes of teaching. This takes what would have otherwise been face-to-face or hybrid teaching and transforms it to become digital education. The Mobile device can help the students continue their lessons through online classes because that is the alternative way to keep learning. Whatsapp Application can help students communicate and share knowledge with their teachers from a distance without face to face. Whatsapp application is then promoted as the alternative way in facing the remote learning situation. WhatsApp has become a shared platform that enhances accessibility, encourages cooperation, and intensifies motivation to take an active part in academic assignments.